Nurses’ Evaluations of the Feasibility and Clinical Utility of the Use of the Critical-Care Pain Observation Tool-Neuro in Critically Ill Brain-Injured Patients - Richard-Lalonde, Melissa; Bérubé, Mélanie; Williams, Virginie; Bernard, Francis; Tsoller, Darina; Gélinas, Céline (Science of Nursing and Health Practices / Science infirmière et pratiques en santé)

(untitled) (Réseau de recherche en interventions en sciences infirmières du Québec (RRISIQ), 2019)
Introduction: The Critical-Care Pain Observation Tool-Neuro (CPOT-Neuro) was derived from the original CPOT to assess pain in brain-injured patients in the adult intensive care unit (ICU). Objective: This study aimed to describe the nurses’ evaluations of the feasibility and clinical utility of the use of the French and English versions of the CPOT-Neuro in critically ill brain-injured adults. Methods: Fifty-nine ICU nurses from two university affiliated trauma centres (Montreal, Canada) were trained to use the CPOT-Neuro. Those who used it at the bedside during the study were invited to complete a self-administered questionnaire about its feasibility and clinical utility. Results: Twenty-seven of the trained ICU nurses (46 %) used the CPOT-Neuro during the study and completed the questionnaire. Feasibility: All nurses agreed that the training duration was sufficient, that the directives of use were clear, and that the tool content was simple to understand. Some nurses disagreed that the tool was quick to use (11.1 %), and easy to complete (7.7 %). Clinical utility: The tool was found useful by most nurses, but some of them disagreed that it was helpful for practice (7.7 %), that it influenced their practice (15.4 %) and that they would recommend it routinely (11.1 %). Responses did not differ between nurses from the two trauma centres who used either the French or the English version of the CPOT-Neuro (Mann-Whitney U tests, p>.05). Discussion and conclusion: The CPOT-Neuro was found to be feasible and useful by ICU nurses. Its implementation into daily practice could optimize pain assessment in critically ill brain-injured patients.